Pengembangan Media Maze Kotaku untuk Menstimulasi Kemampuan Memecahkan Masalah pada Anak Usia 4-5 Tahun - Niken Ayu Saptiwi; Anik Lestariningrum (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2021)
The stage ofpre-operational thinking is when children need learning media that can incorporate a simple mindset, especially in finding solutions to the problems at hand. Children are accustomed to very strict guidance and assistance from adults around them, so they do not have the freedom to make their own choices. Children faced this problem at the PAUD Darussalam Jabon institution. Of the 13 children with cognitive achievement related to problem-solving skills, only four received BSH, while two were in the MB category and seven were BB. A needs analysis was carried out to find the need for learning media that needed to be innovated to foster children's interest in achieving simple problem-solving skills. The research design is R & D by adopting Borg & Gall, which is used onlyup to 4 stages with the limitations of the research, namely potential problems, data collection, product design and design validation. The expected results of the research are prototypes related to the design and guidance of Maze Kotaku learning media that will use in developing children's cognitive abilities to focus on problem-solving. It is hoped that the design of the validated product can use in the next stage